Vancomycin Dosing Regimen in Patients with Hyper-Glomerular Filtration Rate: A Case Report - Abdul-Latif, Maha; Suleiman, Nadin; Wright, Victoria; Sanchez, Jorge (Journal of Pharmacy Practice and Community Medicine, 2026)
Demonstrate a specific vancomycin regimen for patients with hyper-glomerular filtration rate that was used in clinical practice achieving the therapeutic Area Under the Curve (AUC) without nephrotoxicity incidence. 2020 guidelines recommend using the area under the curve to estimate vancomycin therapeutic concentration rather than using trough due to lower nephrotoxicity risk. However, there is insufficient evidence of the optimized vancomycin dose in patients with augmented renal clearance. In this population, vancomycin dosing is challenging because of the unmeasurable factors in the renal function or pharmacokinetics estimation methods; hence, an individualizing vancomycin dose is required to achieve the therapeutic goals. In our case reports, the optimized vancomycin dose regimen was warranted with augmented renal clearance to treat a suspected methicillin-resistant Staphylococcus aureus, by using the AUC-guided dose for the therapeutic concentration estimation. One case received a high vancomycin dose, while the other one was on the standard dose. Additional loading doses were used while continuing their current regimen. Thus, the therapeutic area under the curve was achieved but was close to the lower limit after one dose of additional loading dose without new incidence reports of acute kidney injury hospitalization. In conclusion, optimizing vancomycin dose regimen in patients with augmented renal clearance is still challenging in practice. Using an additional loading dose of vancomycin with continuation of the standard or higher dose of vancomycin, may help in achieving the area under the curve to the recommended therapeutic goal. Further studies are required in these populations.
Keywords: AUC; Hyper-Glomerular Filtration Rate; Pharmacokinetics; Quadriplegia; SCD; Vancomycin